2010
DOI: 10.1186/cc9097
|View full text |Cite
|
Sign up to set email alerts
|

Time course of nitric oxide synthases, nitrosative stress, and poly(ADP ribosylation) in an ovine sepsis model

Abstract: IntroductionDifferent isoforms of nitric oxide synthases (NOS) and determinants of oxidative/nitrosative stress play important roles in the pathophysiology of pulmonary dysfunction induced by acute lung injury (ALI) and sepsis. However, the time changes of these pathogenic factors are largely undetermined.MethodsTwenty-four chronically instrumented sheep were subjected to inhalation of 48 breaths of cotton smoke and instillation of live Pseudomonas aeruginosa into both lungs and were euthanized at 4, 8, 12, 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
44
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 33 publications
3
44
0
Order By: Relevance
“…In a peritonitis-induced ovine septic shock model, Su et al (30) showed that the selective iNOS inhibitor, BYK191023, blunted the increase in pulmonary artery pressure and improved gas exchange, microcirculation, and tissue metabolism. Similar findings with selective iNOS inhibition were observed in an ovine sepsis model induced by smoke inhalation with lung installation of bacteria (40,41) and in a porcine bacteremia model (42). These studies indicate that iNOS inhibition may exert its positive effects by reducing eNOS overproduction.…”
Section: Discussionsupporting
confidence: 83%
“…In a peritonitis-induced ovine septic shock model, Su et al (30) showed that the selective iNOS inhibitor, BYK191023, blunted the increase in pulmonary artery pressure and improved gas exchange, microcirculation, and tissue metabolism. Similar findings with selective iNOS inhibition were observed in an ovine sepsis model induced by smoke inhalation with lung installation of bacteria (40,41) and in a porcine bacteremia model (42). These studies indicate that iNOS inhibition may exert its positive effects by reducing eNOS overproduction.…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, we now utilized the corresponding mouse model of pulmonary infection to compensate for this limitation. However, we found that the time course of protein contents of inflammatory cytokines in lung tissue in mice was similar to the time course of IL-8 protein content in sheep in the previous study [17]. This finding further suggests that the injuries in both animal models trigger similar pathophysiological reactions in the lung.…”
Section: Discussionsupporting
confidence: 81%
“…We have previously described the time changes in NO synthases, nitrosative stress, and poly(ADP ribosylation) in an ovine model of pulmonary sepsis [17]. Unfortunately, in this study, we were not able to measure cytokine concentrations, other than IL-8, because most available antibodies for biomolecular measurements do not cross-react with sheep tissue.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Key mechanisms of vascular dysfunction include the activation of neutrophils and the subsequent interaction with the endothelium (diapedesis, "rolling and sticking") (20) as well as the increased production of nitric oxide via stimulation of the inducible nitric oxide synthase and reactive nitrogen species, such as peroxynitrite (22). In addition, mediators released by the endothelial cells, like VEGF and angiopoietin-2, contribute to the development of vascular leakage (25,32).…”
mentioning
confidence: 99%